Impact of COVID-19 Pandemic on Mechanical Reperfusion in ST-Segment-Elevation Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention: A Multicenter Retrospective Study From a Non-epicenter Region - Mao, Qi; Zhao, Jianhua; Li, Youmei; Xie, Li; Xiao, Han; Wang, Ke; Qiu, Youzhu; Chen, Jianfei; Xu, Qiang; Xu, Zhonglin; Yu, Yang; Zhang, Ying; et al. (Frontiers in Cardiovascular Medicine, 2021)
Objective: The COVID-19 pandemic placed heavy burdens on emergency care and posed severe challenges to ST-segment-elevation myocardial infarction (STEMI) treatment. This study aimed to investigate the impact of COVID-19 pandemic on mechanical reperfusion characteristics in STEMI undergoing primary percutaneous coronary intervention (PPCI) in a non-epicenter region. Methods: STEMI cases undergoing PPCI from January 23 to March 29 between 2019 and 2020 were retrospectively compared. PPCI parameters mainly included total ischemic time (TIT), the period from symptom onset to first medical contact (S-to-FMC), the period from FMC to wire (FMC-to-W) and the period from door to wire (D-to-W). Furthermore, the association of COVID-19 pandemic with delayed PPCI risk was further analyzed. Results: A total of 14 PPCI centers were included, with 100 and 220 STEMI cases undergoing PPCI in 2020 and 2019, respectively. As compared to 2019, significant prolongations occurred in reperfusion procedures (P<0.001) including TIT (420 min vs. 264 min), S-to-FMC (5h vs. 3h), FMC-to-W (113 min vs. 95 min) and D-to-W (83 min vs. 65 min). Consistently, delayed reperfusion surged including TIT≥12h (22.0% vs.3.6%), FMC-to-W ≥120 min (34.0% vs. 6.8%) and D-to-W ≥90 min (19.0% vs. 4.1%). During the pandemic, the patients with FMC-to-W≥120 min had longer durations in FMC to ECG completed (6 min vs. 5min, P=0.007), FMC to DAPT (24 min vs. 21 min, P=0.001), catheter arrival to wire (54 min vs. 43 min, P<0.001) and D-to-W (91 min vs. 78min, P<0.001). The pandemic was significantly associated with high risk of delayed PPCI (OR=7.040, 95%CI 3.610-13.729, P<0.001). Conclusions: Even in a non-epicenter region, the risk of delayed STEMI reperfusion significantly increased due to cumulative impact of multiple procedures prolongation.